Molecular phylogenetics of ponerine ants (Hymenoptera: Formicidae: Ponerinae) - Schmidt, Chris (Zootaxa, 2013)
Recent molecular phylogenetic studies of ants (Hymenoptera: Formicidae) have revolutionized our understanding of how these ecologically dominant organisms diversified, but detailed phylogenies are lacking for most major ant subfamilies. I report the results of the first detailed phylogenetic study of the ant subfamily Ponerinae, a diverse cosmopolitan lineage whose properties make it an attractive model system for investigating social and ecological evolution in ants. Molecular sequence data were obtained from four nuclear genes (wingless, long-wavelength rhodopsin, rudimentary [CAD], 28S rD-NA; total of 3.3 kb) for 86 ponerine taxa, representing all three ponerine tribes, 22 of the 28 currently recognized genera, and 14 of the 18 informal subgenera of Pachycondyla, a heterogeneous grouping whose monophyly is doubtful on mor-phological grounds. Phylogenetic reconstructions using maximum likelihood and Bayesian inference support the mono-phyly of Ponerinae and tribe Platythyreini, but fail to support the monophyly of the large tribe Ponerini due to its inclusion of the unusual genus Thaumatomyrmex. Pachycondyla is inferred to be broadly non-monophyletic. Numerous novel ge-neric and suprageneric relationships are inferred within Ponerini, which was found to consist of four major multi-generic clades (the Ponera, Pachycondyla, Plectroctena and Odontomachus genus groups) plus the single genera Hypoponera and Harpegnathos. Uncertainty remains in some regions of the phylogeny, including at the base of Ponerini, possibly reflect-ing rapid radiation. Divergence dating using a Bayesian relaxed clock method estimates an origin for stem Ponerinae in the upper Cretaceous, a major burst of diversification near the K/T boundary, and a rich and continual history of diversi-fication during the Cenozoic. These results fail to support the predictions of the “dynastic-succession hypothesis” previ-ously developed to explain the high species diversity of Ponerinae. Though model-based reconstructions of historical biogeography and trait evolution were not attempted in this study, the phylogeny suggests that ponerine evolution was marked by regionalized radiations and frequent faunal exchange between major biogeographic provinces. The reported results also imply multiple origins of cryptobiotic foraging, mass raiding behavior, and gamergate reproduction within Ponerinae, highlighting the value of the subfamily as a model for studying the incipient evolution of these and other eco-logical and behavioral traits.